Um manuscrito alcobacense reencontrado - Filipe Alves Moreira (Medievalista)
This work systematizes the known data on the manuscript tradition of the Summary of the chronicles of the Portuguese Kings by Cristóvão Rodrigues Acenheiro, including the identification of the manuscripts used by the only existing edition (Academia das Ciências, 1824). It is argued that the base text of this edition was a 16th century copy belonging to the monastery of Alcobaça which, after being used by the Academia das Ciências, belonged to the Countess of Azambuja and it is currently in the Arquivo Distrital de Braga.